Influence of «sensory prehistory» on the ambiguous stimuli processing in the human brain - Kuc, Alexander; Maksimenko, Vladimir; Hramov, Aleksandr (Luchshie medit͡s︡inskie t͡s︡entry Moskvy, 2022)
Purpose of this work is to study the effect of previous sensory information on the brain’s processing of current visual stimuli. Bistable images (Necker cubes) with a high degree of ambiguity (HA) and a low degree of ambiguity (LA) were used as visual stimuli. Methods. In this paper, we used wavelets to identify features of the brain activity signals. A multivariate analysis of variance was used to compare behavioral characteristics. Spectral power and event-related spectral perturbations were compared via a cluster-based permutation test using the FieldTrip package for Matlab. Results. We found that when the HA stimuli followed the LA stimuli, the activity of neurons in the sensory areas decreased in the early processing stage but increased in the later stages. This result confirmed the hierarchical organization of processing, where the low levels processed the details of the stimulus, and the high levels represented its interpretation. We supposed that processing of HA and LA stimuli was similar at low levels due to their similar morphology. Therefore, the brain might use the LA stimulus template at low levels to reduce the demands when processing the details of the HA stimulus. When the LA stimulus followed the HA stimulus, a weakened response in the sensory regions accompanied a high response in the frontal cortex. It reflected activation of the top-down cognitive functions, detecting a mismatch between the LA stimulus and the HA stimulus template. Conclusion. These results expanded the existing knowledge about the sensory processing mechanisms.